Cases for Medical Physiology Small-Group Discussions - Rob Zachow; Stephen Schneider; Suzanne Kabis; Kiron Das; William Zehring (Association of American Medical Colleges, 2007)
Abstract Introduction Early on in medical training it is important for learners to understand the level of knowledge necessary to provide quality patient care, as well as what will be expected of them on the United States Medical Licensing Examination, Step 1. In order to address this, a team of clinical faculty at Robert Wood Johnson Medical School created this set of cases to integrate clinical and basic science knowledge through detailed clinical presentations. Methods Directly following the presentation of relevant lecture material, students have a 50-minute facilitated small-group session to work through a case. The case topics include congenital adrenal hyperplasia, Crohn's disease, metabolic syndrome, myasthenia gravis, nephrotic syndrome, polycystic ovary syndrome (PCOS), and polycystic kidney disease. Results We have successfully incorporated these cases into two first-year medical student courses. We have also piloted the PCOS case in a Physician's Assistant curriculum, which was met with a high degree of enthusiasm from the students. Discussion By adjusting the topics for discussion, these cases can be adapted for use in a variety of first- and second-year medical school courses, as well as other health professional curricula.